2009
DOI: 10.35196/rfm.2009.4.289-294
|View full text |Cite
|
Sign up to set email alerts
|

Características Deseables De Plantas De Pepino Crecidas en Invernadero E Hidroponía en Altas Densidades De Población

Abstract: La contribución de algunos caracteres morfológicos de la planta de pepino (Cucumis sativus L.) en el rendimiento por planta y por unidad de superficie, factibles de incorporarse a un arquetipo idóneo para su manejo en un sistema de producción basado en despuntes tempranos de la yema terminal (plantas de 1 m de altura) y alta densidad de población, se evaluó en ambientes poco restrictivos (invernadero e hidroponía). Se establecieron dos experimentos; en el Experimento I se evaluaron 11 variedades en dos densida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…These differences may be primarily related to the amount of intercepted radiation, the efficiency of its transformation, and the duration of the leaf area. As observed by Ortíz et al (2009) in cucumber cultivation in greenhouses and hydroponics, where this effect is attributed to a lower level of shading between them that allowed them a greater and better radiation interception and therefore greater production of photoassimilates per plant.…”
Section: Resultsmentioning
confidence: 74%
“…These differences may be primarily related to the amount of intercepted radiation, the efficiency of its transformation, and the duration of the leaf area. As observed by Ortíz et al (2009) in cucumber cultivation in greenhouses and hydroponics, where this effect is attributed to a lower level of shading between them that allowed them a greater and better radiation interception and therefore greater production of photoassimilates per plant.…”
Section: Resultsmentioning
confidence: 74%
“…Leaf area can be directly related to biomass accumulation and plant performance because it allows better capture of radiant energy. Ortiz-Cereceres et al (2009) found a positive correlation between leaf area and cucumber yield, observing a production of two more fruits per plant in varieties with a larger leaf area. Ramírez-Vargas (2019) found leaf area values between 433 and 563 cm 2 plant -1 , much lower than the leaf area (4798 cm 2 plant -1 ) reported by Da Silva et al (2011) in cucumber plants.…”
Section: Leaf Areamentioning
confidence: 88%